\(A=\dfrac{5}{3}x^2y^3\)
Thay \(x=-1;y=-1\) vào biểu thức A ta được :
\(\dfrac{5}{3}\cdot\left(-1\right)^2\cdot\left(-1\right)^3=-\dfrac{5}{3}\)
Vậy : ...
thay x =-1 , y=-1 vào biểu thức A ta đc
A=\(\dfrac{5}{3}\left(-1\right)^2\left(-1\right)^3=\dfrac{5}{3}.1.\left(-1\right)=-\dfrac{5}{3}\)
thay x =-1 , y=-1 vào biểu thức A
ta đc:\(A=\dfrac{2}{3}.\left(-1\right)^2.\left(-1\right)^3-\dfrac{5}{2}\left(-1\right)^2.\left(-1\right)^3+\dfrac{7}{2}.\left(-1\right)^2.\left(-1\right)^3=\dfrac{5}{3}\left(-1\right)^2\left(-1\right)^3\\ A=\dfrac{-2}{3}-\dfrac{5}{2}+\dfrac{-7}{2}=\dfrac{-5}{3}\\ A=\dfrac{-2}{3}-1=\dfrac{-5}{3}\\ A=\dfrac{-5}{3}=\dfrac{-5}{3}\)